1999
DOI: 10.1002/(sici)1097-4652(199907)180:1<97::aid-jcp11>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-regulated stresses cause degradation of DNA topoisomerase II? by inducing nuclear proteasome during G1 cell cycle arrest in cancer cells

Abstract: The glucose-regulated stress response of cancer cells leads to a decreased expression of DNA topoisomerase IIalpha (topo IIalpha) and a cell cycle arrest at the G1 phase. In this study, we found that the topo IIalpha decrease occurred specifically during the G1 arrest in human colon adenocarcinoma HT-29 cells. The intracelluar level of topo IIalpha in HT-29 cells was relatively constant regardless of cell cycle position in the exponentially growing state, determined using a centrifugal elutriation technique an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Our present findings would be useful in elucidating the mechanisms of topo II␣ degradation in these situations. It should then be noted that topo II␣ often escapes the quiescence-and cell cycle-dependent regulation in tumor cells (15,41,42), suggesting that deregulated proteolysis of topo II␣ may be involved in tumor development by analogy with p27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our present findings would be useful in elucidating the mechanisms of topo II␣ degradation in these situations. It should then be noted that topo II␣ often escapes the quiescence-and cell cycle-dependent regulation in tumor cells (15,41,42), suggesting that deregulated proteolysis of topo II␣ may be involved in tumor development by analogy with p27…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, topo II␣ degradation under glucose starvation has been observed in a variety of solid tumor lines, even in cells where the cell cycle-dependent regulation is abrogated (15,18). Thus, the GRDD-and MPN-dependent degradation of topo II␣ might be particularly important for cellular adaptation to severe stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the synchronized culture, we trapped cells in M phase of the cell cycle by treating them with 40 ng of nocodazole/ml (Wako Pure Chemical Industries, Osaka, Japan) for 9 h, collected cells by gentle pipetting, and reseeded them in fresh culture medium (28,29). Populations of G1-and S-phase cells constituted the majority (typically 60 -70%) of the total cell population at 3 h and 9 h after the release, respectively (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that 2DG and EF provoke ER stress by utilizing parallel pathways. Kim et al (1999) have reported that, in an attempt to maintain ER homeostasis, cells undergoing glycolytic stress elevate their level of nuclear proteasomal activities raising the possibility that EF synergize with 2DG in increasing ER stress by inhibiting 2DG-induced proteasomal function. This may also explain why combination treatment is more effective in MDA-MB-231 cells than in MCF-7 cells, since the former are more sensitive to proteasomal inhibition.…”
Section: Discussionmentioning
confidence: 99%